(untitled) (Research, Society and Development, 2020)
Virola surinamensis is an Amazonian species of the Myristicaceae family, with significant potential for the restoration of degraded areas, in addition to being one of the species currently most explored by the timber industry in the Amazon estuary. However, seed germination and seedling production are hampered by the presence of embryonic dormancy in the species, requiring the use of methods to assist their germination processes. The objective of this study was to evaluate the effect of the application of gibberellic acid (GA3) on seed germination and on the initial biomass production of Virola surinamensis. The design used was completely randomized, with the seeds immersed for 24h in different concentrations of gibberellic acid (0, 500, 600, 700 and 800 ppm) with five repetitions of 25 seeds, using as sand substrate and tanned sawdust (1: 1 v/v). Analysis of variance and regression of the results was performed and the treatment averages were compared by the Tukey test at the level of 5% probability (p <0.05). The 600 ppm dosage was more effective in increasing the emergence percentage (E) by 28.2%, the emergence speed index (IVE) in 0.246, germination (G) in 30.2% and the accumulation total biomass (MST) at 3.704 g / seedlings and, for the days to start the emergency (DIE), the 800 ppm treatment promoted a 27% reduction in the average emergency time. All concentrations of gibberellic acid positively influenced the germination processes and the accumulation of total biomass in the seedlings of Virola surinamensis.